MICROSTRUCTURE AND PHYSICAL PROPERTIES OF SnO₂ THIN FILMS - Madrakhimov Muminzhon Mukhidinovich; Khidirov Dadakhon Sherkozievich (Western European Studies, 2025)
This article investigates the microstructure, electrical and optical properties, and gas sensitivity of AsGa-doped SnO₂ thin films obtained by thermal evaporation in vacuum.
Keywords: SnO₂ thin films; electron microscopy; gas sensitivity